Sulfidogenic activity of sulfate and sulfur reducing bacteria under the influence of metal compounds - O. M. Moroz; S. O. Hnatush; O. V. Tarabas; C. I. Bohoslavets; G. V. Yavorska; B. M. Borsukevych (Biosystems Diversity, 2018)
Due to their high content in natural environments, heavy metals exhibit toxic effects on living organisms, which leads to a decrease in the biological diversity and productivity of ecosystems. In niches with low oxidation reducing potential, sulfate and sulfur reducing bacteria carry out the reducing transformation of oxidized sulfur compounds with the formation of significant amounts of hydrogen sulfide. H2S produced by bacteria interacts with metal ions, precipitating them in the form of sulfides. The aim of this work was to investigate the influence of lead, cuprum (II), iron (II) and manganese (II) salts on the production of hydrogen sulfide by bacteria of the Desulfovibrio and Desulfuromonas genera, isolated from Yavorivske Lake, and to evaluate the efficiency of their use for purifying media, enriched with organic compounds, from hydrogen sulfide and heavy metals. The content of heavy metal ions in the water of Yavorivske Lake was determined by the spectrophotometric method. The bacteria were grown for 10 days at 30 °C in the Kravtsov-Sorokin medium under anaerobic conditions. To study the influence of metal ions on bacteria growth and their H2S production, cells were incubated with metal salts (0.5–4.0 mM), washed and grown in media with SO42– or S0. To determine the level of metal ions binding by H2S, produced by bacteria, cells were grown in media with metal compounds (0.5–4.0 mM), SO42– or S0. Biomass was determined by turbidimetric method. In the cultural liquid the content of H2S was determined quantitatively by spectrophotometric method, and qualitatively by the presence of metal cations. The content of metal sulfides in the growth medium was determined by weight method. Sulfate and sulfur-reducing bacteria were resistant to 2.0 mM Pb(NO3)2, 2.5 mM CuCl2, 2.5 mM FeCl2 × 4H2O and 2.0 mM MnCl2 × 4H2O, therefore they are promising for the development of biotechnologies for the purification of water resources contaminated by sulfur and metal compounds. When present in a medium with sulfates or sulfur of 1.0–1.5 mM lead, cuprum (II), iron (II) or manganese (II) ions, they almost completely bind with the H2S produced by bacteria in the form of insoluble sulfides, which confirms the negative results of qualitative reactions to their presence in the cultural liquid.